2020
DOI: 10.1038/s41467-020-16593-y
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasites regulate intra-erythrocytic development duration via serpentine receptor 10 to coordinate with host rhythms

Abstract: Malaria parasites complete their intra-erythrocytic developmental cycle (IDC) in multiples of 24 h suggesting a circadian basis, but the mechanism controlling this periodicity is unknown. Combining in vivo and in vitro approaches utilizing rodent and human malaria parasites, we reveal that: (i) 57% of Plasmodium chabaudi genes exhibit daily rhythms in transcription; (ii) 58% of these genes lose transcriptional rhythmicity when the IDC is out-of-synchrony with host rhythms; (iii) 6% of Plasmodium falciparum gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(106 citation statements)
references
References 74 publications
7
84
1
2
Order By: Relevance
“…Whether an infection exhibits synchronous or asynchronous replication is not dictated purely by the host because, for example, the opposing IDC schedules of P. berghei and P. chabaudi are apparent when each species infects the same age, sex, and strain of laboratory mice. This observation, coupled with recent discoveries of parasite control of the IDC schedule [ 25 27 ] suggests the degree of synchrony and the timing of the IDC are at least in part controlled by parasites. If so, it raises the possibility that a synchronous or asynchronous IDC are different parasite strategies that have evolved by natural selection because they enhance parasite fitness [ 18 ].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Whether an infection exhibits synchronous or asynchronous replication is not dictated purely by the host because, for example, the opposing IDC schedules of P. berghei and P. chabaudi are apparent when each species infects the same age, sex, and strain of laboratory mice. This observation, coupled with recent discoveries of parasite control of the IDC schedule [ 25 27 ] suggests the degree of synchrony and the timing of the IDC are at least in part controlled by parasites. If so, it raises the possibility that a synchronous or asynchronous IDC are different parasite strategies that have evolved by natural selection because they enhance parasite fitness [ 18 ].…”
Section: Introductionmentioning
confidence: 82%
“…This finding supports recent studies suggesting that across Plasmodium spp. features of the IDC schedule are under the control of parasite genes [ 25 27 ], rather than directly generated by the host, by for example selectively removing certain IDC stages at certain times of day. Why some species are impervious to the daily rhythms of their hosts and vectors remains mysterious.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Subudhi et al 42 demonstrated that coordination of the parasite cell cycle to host rhythms plays a central role in the cycling gene expression associated with essential processes for parasite erythrocytic development.…”
Section: Discussionmentioning
confidence: 99%
“…Another Plasmodium GPCR-like protein, PfSR10, exhibits a circadian transcription profile with peak expression at two time points during the IED, the first after 8 h and the second after 32 h post-invasion. Disrupting its orthologous gene in P. chabaudi , PcSR10, shortens the IED by 2–3 h in mice [ 63 ]. Similarly, it has been reported that Plasmodium parasites exhibit intrinsic rhythm in more than 75% genes during IED, increasing the complexity of host–parasite periodicity [ 64 , 65 ].…”
Section: Melatonin Triggers a Signalling Cascade In Plasmodium Parmentioning
confidence: 99%